Synthesis and Evaluation of the Antibacterial Effect of Titanium Dioxide Nanoparticles in Comparison with Ampicillin, Colistin, and Ertapenem on Staphylococcus aureus (Journal of Pharmaceutical Negative Results, 2019)
Objectives: Today, the emergence of antibiotic-resistant strains and the acquisition of antibiotic resistance have caused many problems inthe treatment of Staphylococcus aureus infection and is one of the most important health issues. At present, nanotechnology has a significantimpact on the various fields including pharmacology, health, medicine, and food. This study aimed to synthesize the titanium dioxidenanoparticles (Tio2NPs) and its antibacterial effect on S. aureus compared with conventional antibiotics. Materials and Methods: In thisstudy, Tio2NPs were tested on S. aureus compared with a number of antibiotics. First, Tio2NPs were synthesized. The shape and size of theparticles as well as the synthesis quality were investigated using scanning electron microscopy (SEM), atomic force microscopy (AFM),dynamic light scattering, zeta potential and X‑ray diffraction, and Fourier‑transform infrared spectroscopy. The antimicrobial effect of Tio2NPs on S. aureus strain (ATCC 12600) was then studied by disc diffusion method. Antibiotics of ampicillin, colistin, and ertapenem wereused as control group. Results: Based on the results and given that the polydispersity index of the samples was below 0.5 (0.466), the othersample was estimated at 347.9 nm. The zeta potential of Tio2 sample was estimated at −9.48 indicating the stability of the nanoparticle and itssuspension in a suitable amount per unit of time in the solution. The results of the AFM showed that the lower mean value obtained for theTio2NPs was 0.5 nm, and the growth of the nanoparticles was noticeable in some regions and uniform and low in some others. The result ofSEM showed that the size of the nanoparticle was 28.45–34.14 nm. The best inhibition zone diameter was obtained for ampicillin (30.66 mm),followed by ertapenem (15 mm) and Tio2 (10 mm). Colistin without inhibition zone was identified as ineffective group. Conclusion: Due tothe development of drug resistance to antibiotics, the production and synthesis of antimicrobial agents is one of the requirements of the currenttime. Due to the excellent synthesis of Tio2 and the presence of very fine nanoparticles, it can be used as a strong antimicrobial compound,especially on S. aureus infection.Keywords: Antibiotic, disease, inf